2018
DOI: 10.1111/cpr.12471
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of receptors of advanced glycation end products ameliorates diabetic osteogenesis of adipose‐derived stem cells through DNA methylation and Wnt signalling pathway

Abstract: Our results demonstrate that AGEs-RAGE signalling inhibits the osteogenic potential of ASCs under osteoinductive conditions by modulating DNA methylation and Wnt signalling. FPS-ZM1 can rescue the negative effects of AGEs and provide a possible treatment for bone tissue regeneration in patients with diabetic osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 46 publications
4
65
0
Order By: Relevance
“…Additionally, by testing ST2 cells and human MSCs, it was shown that AGEs interact with RAGE and increase expression and secretion of TGF- β , which can suppress stromal cell mineralization [60]. The interaction of AGE–RAGE seems to be the dominant way, as their inhibitory effects on Wnt signaling pathway is reversible with the RAGE receptor antagonist FPS-ZM1 [72]. RAGE suppresses cell proliferation through suppression of Wnt, PI3K, and ERK signaling pathways [73].…”
Section: Age/rage and The Bone Remodeling Processmentioning
confidence: 99%
“…Additionally, by testing ST2 cells and human MSCs, it was shown that AGEs interact with RAGE and increase expression and secretion of TGF- β , which can suppress stromal cell mineralization [60]. The interaction of AGE–RAGE seems to be the dominant way, as their inhibitory effects on Wnt signaling pathway is reversible with the RAGE receptor antagonist FPS-ZM1 [72]. RAGE suppresses cell proliferation through suppression of Wnt, PI3K, and ERK signaling pathways [73].…”
Section: Age/rage and The Bone Remodeling Processmentioning
confidence: 99%
“…FPS-ZM1 rescues AGE-induced loss of the osteogenic potential of adipose-derived stem cells (ASCs) in a diabetic environment [41]. Irbesartan, an agiotensin II type 1 receptor blocker, has anabolic bone effects in diabetes, inhibiting the deleterious effects of oxidative stress mediated by AGEs/RAGE [42].…”
Section: Ragementioning
confidence: 99%
“…Axin2 negatively regulates β-catenin and is a target of Wnt/β-catenin signaling ( Bernkopf et al, 2019 ). LEF1, binding to Wnt response elements to provide docking sites for β-catenin is a Wnt signaling pathway marker ( Zhang M. et al, 2018 ). A growing body of evidence suggests that susceptibility genes of Parkinson’s disease are associated with Wnt signaling regulation ( Berwick and Harvey, 2014 ; L’Episcopo et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%